Liturgia jako antycypacja eschatologicznego święta - Agnieszka Makarewicz (Wrocławski Przegląd Teologiczny)
The fundamental issue of the article is an attempt to answer the question whether the main article of the Church’s faith: „I believe in eternal life”, is expressed in the texts of The Roman Mass Book for Polish Dioceses. The author analyses the mass texts according to the eschatological key. The earthly Church is the Church of desire and deep hope. Participation in the Eucharist is the confirmation of the Church’s belief in the eternal life and, at the same time, anticipation of the eschatological communion of the earthly and heavenly Church. The author points out that the liturgical action and the content of the mass prayers brings the earthly Church closer to the Holy Mystery, which becomes its experience during the Eucharist. The answer to the initial question is positive. In the texts of the Roman Mass Book one can find numerous references to the article of faith: „I believe in eternal life”. The desire for eternal life and the foretaste of this experience accompany the members of the earthly Church from the very beginning of the Eucharist and pervades all its parts.